Demand Shocks and Open Economy Puzzles - Bai, Yan; RÍos-Rull, José-VÍctor (American Economic Review, 2015)
We pose good markets frictions on top of an otherwise standard two-country international real business cycle (IRBC) model. Shopping for goods takes effort, which prevents perfect matching between customers and producers. An increase in search effort implies increased measured productivity. Demand shocks increase expenditures and search effort simultaneously increasing output, consumption, productivity, and the trade deficit and appreciating the real exchange rate. Thus we solve the Backus-Smith puzzle and we show that the cross country correlation of consumption is higher than that of output. Standard IRBC models cannot account for these puzzles along with movements in TFP.